High Resolution Stratigraphy of the Lower Silurian (Rhuddanian-Aeronian) Paleotropical Neritic Carbonates, Anticosti Island, Québec - Daoust, Pascale (Université d'Ottawa / University of Ottawa, 2017)
Anticosti Island, located in Eastern Canada, displays one of the most complete, best exposed, and most fossiliferous carbonate successions spanning the Ordovician-Silurian (O/S) Boundary in the World. This study develops a new high-resolution framework for the post End-Ordovician extinction strata (~ 260 m thick) exposed in coastal outcrops and recovered from a continuous drill core (La Loutre #1), both located in the western part of the island. In total, eight facies, all associated with a storm-dominated carbonate system, were recognized and organized into a multi-order depositional cycles. A new high resolution isotopic curve with more than 300 data points from well-preserved bulk micrite samples covers the late Hirnantian to Early Aeronian time interval and corresponds to the upper Ellis Bay, Becscie, Merrimack and lower Gun River formations. Two distinct positive carbon isotope excursions are present in the late Hirnantian part of the Ellis Bay Formation (+5‰) and in the lower Aeronian part of the Gun River Formation (+2‰). These positive isotopic carbon excursions provide a distinctive chemostratigraphic signature for regional and global correlations with other O/S sections. Like the Quaternary δ18O marine signal, our δ18O record is largely coupled with multi-order cyclic facies changes. This study demonstrates the importance of glacio-eustasy following the End-Ordovician glacial maxima as one of the primary factors controlling the stratigraphic architecture of paleotropical neritic carbonates during the Early Silurian.
Keywords: Stratigraphy; Carbonates; Chemostratigraphy; Cyclostratigraphy; Ordovician-Silurian boundary